Metabolic Syndrome as a Risk Factor for Coronary Heart Disease (Review) (Eurasian Medical Research Periodical, 2022)
Chronic heart failure (CHF) is a major medical and social problem. The increase in morbidity is due to both an increase in the life expectancy of the population and the influence of risk factors that contribute to the development and increase of circulatory failure. The combination of several ather 0genic factors (abdominal obesity, insulin resistance, arterial hypertension, hyperglycemia, dyslғ